Development and Initial Biogeochemical Applications of Compound-Specific Sulfur Isotope Analysis - Greenwood, Paul; Amrani, A.; Sessions, A.; Raven, M.; Holman, Alex; Dror, G.; Grice, Kliti; Mcculloch, M.; Adkins, J. (The Royal Society of Chemistry, 2014)
Compound-specific isotope analysis (CSIA) has been extended to the 32S and 34S stable isotopes of sulfur (δ34S) through the combination of gas chromatography (GC) and multi-collector inductively coupled mass spectrometry (ICPMS). The molecular level resolution of sulfur-CSIA is greatly expanding the biogeochemical applications of existing sulfur isotope methods, particularly with respect to organic sulfur compounds. Sulfur participates in a variety of important biogeochemical and redox processes, with distinctive isotopic fractionations accompanying many of these. For example, hydrogen sulfide produced during microbial sulfate reduction can be strongly depleted in 34S (up to 66‰ in δ34S) compared to the source sulfate. An improved understanding of sulfur biogeochemistry at the molecular level will assist in the interpretation of studies of sulfur cycling associated with the modern and paleo-environments. A comparison of δ34S values between organic and inorganic sulfur species may help to illuminate the complex role of sulfur in sedimentary organic diagenesis and the pathways of organic sulfur formation. The δ34S values of individual organic sulfur compounds from natural settings can be currently measured by GC-ICPMS with impressive accuracy, precision (<0.5‰) and sensitivity (≥20 pmol S) over a broad range of analyte volatility. The new sulfur-CSIA capability has already been used to study pathways of early diagenetic organic sulfurisation, volatile sulfur emission from the oceans, oil correlations, thermochemical sulfate reduction of petroleum hydrocarbons, and the relationship between OSCs and mineralising sulfides of large metal deposits.